Categorising the term of Personal Health Record – a Systematic Review and Analysis of the Term used in Literature - Koskinen Jani; Rantanen Minna (Inderscience Publishers, 2025)
The purposes of this article are to investigate how the term 'personal health record' (PHR) is used in the literature and to offer a proposal for future uses of the term. A systematic literature review was conducted to identify and analyse the use of PHR definitions. Four databases were reviewed: ScienceDirect, IEEE Xplore, ProQuest and PubMed. We found and screened a total of 1,781 articles published between 2000 and 2017, only 233 (19%) of which defined PHR. These definitions often conflicted with or even contradicted one another. Even the most commonly used definitions did not properly define PHR, focusing instead on specific attributes and functionalities of PHRs or setting questionable limitations on what should be seen as a PHR. Thus, a clear and systematic categorisation for defining PHRs is needed, and one is offered in this article. This kind of hierarchical definition allows for flexible use of the term. When a term is defined with different levels of abstraction, it offers a flexible focus for other purposes while still fulfilling the need for a clear definition.